A new species of Cyrtodactylus Gray, 1827 (Reptilia: Squamata: Gekkonidae) from Kokrajhar District, Assam, India - Basfore, Bijay; Bharali, Manmath; Barman, Rathin; Deka, Sanatan; Islam, Nazrul; Deb, Arnab; Bohra, Sanath Chandra; Bhattacharjee, Rupankar; Das, Madhurima; Hazarika, Arup Kumar; Naorem, Anjana Singha; Purkayastha, Jayaditya (Zootaxa, 2026)
We herein describe a new species of Cyrtodactylus from Kachugaon, in the Kokrajhar District of Assam, India. Morphological characteristics combined with ND2 mitochondrial gene sequence data support its placement within the Cyrtodactylus khasiensis group, identifying Cyrtodactylus raimonaensis sp. nov. as the sister lineage to Cyrtodactylus septentrionalis. It is characterised by a moderate adult size (maximum SVL 71.1 mm), rounded, bluntly conical, and weakly keeled dorsal tubercles arranged in 20 or 21 longitudinal rows, and 36–38 paravertebral tubercles between the axilla and groin. Other diagnostic features include 32–38 mid-ventral scale rows, 13 precloacal pores in male, 13 precloacal pits in females, 17–20 subdigital lamellae beneath the fourth toe, absence of a single row of transversely enlarged subcaudal scales, 7 or 8 pairs of dark dorsal blotches between the axilla and groin, and a tail bearing alternating dark and light bands.